HIGH PERFORMANCE HUMAN RESOURCE PRACTICES AND CORPORATE ENTREPRENEURSHIP: THE MEDIATING EFFECT OF MIDDLE MANAGERS KNOWLEDGE COLLECTING AND DONATING BEHAVIOUR - Michael Mustafa; John J. Richard; Hazel Melanie Ramos (Asian Academy of Management Journal, 2013)
This study develops a mediation model in which high-performance human resource practices affect corporate entrepreneurship through two dimensions of knowledge sharing: knowledge collecting and knowledge donating. In a sample of 292 middle managers from Malaysia, we find that high-performance human resource practices relate positively to corporate entrepreneurship, and this relation is mediated by knowledge sharing. The results suggest that the willingness of middle managers to engage in knowledge sharing serves as a partial mediator to attenuate this positive relationship. However, an interesting outcome from this study is that although high-performance human resource practices are positively related to the willingness of middle managers to collect and donate knowledge, only middle managers' willingness to donate knowledge was found to partially mediate the relationship between high-performance human resource practices and corporate entrepreneurship. We discuss the theoretical and managerial implications for human resource management research and practice.